ANALISIS KERAGAMAN MORFOMETRIK DAN GENETIK PADA STRAIN IKAN MAS (Cyprinus carpio) - Didik Ariyanto; Imron Imron (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of this research was to identify the morphological and genetical variability in four strains of common carp (Cyprinus carpio) i.e. Majalaya, Rajadanu, Wildan and Sutisna. The study was conducted by analysis of truss morphometric and electrophoresis. Principal Component Analysis (PCA) was conducted to explore the patterns of body shape variability and the grouping among strains. The Degree of polymorphism, heterozigosity and genetic distance were used to identify the structure of populations. The results showed that the truss morphometric on head and caudal peduncle were the most contribute cells to distinguish the variability among strains. Based on genetic parameters analysis, strain of Rajadanu, Sutisna and Wildan were originaly coming from one strain with genetic distance about 0.0018 to Majalaya strain. Body shape similarity of Wildan and Majalaya strains was more influenced by their environment.